Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

Using elimination, substitution solve A A. 3x - 9y = 3 6x - 3y = (-24)

Biology
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SEE EXPERT ANSWER

To see the expert answer you'll need to create a free account at Brainly

it belongs in the math section
but okay. 3x - 9y = 3 lets get x alone. 3x=3+9y

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

yeah i dont care
1)Elimination by coefficient method 3x - 9y = 3 .....( i ) 6x - 3y = - 24 ...( ii ) Multiplying ( i ) by 2,we get 6x - 18y = 6 .... ( iii ) Subtracting ( ii ) from ( iii ),we get 6x - 18y = 6 6x - 3y = - 24 (-) (+) (+) --------------------- - 15y = 30 y = - 2 Substituting y = - 2 in ( ii ),we get 6x - 3(- 2) = - 24 6x + 6 = - 24 6x = - 30 x = - 5 x = - 5 and y = - 2 is the solution of given simultaneous equations. 2)Substitution method 3x - 9y = 3 Dividing throughout by 3,we get x - 3y = 1 x = 1 + 3y ..... ( i ) 6x - 3y = - 24 .....( ii ) Substituting ( i ) in ( ii ),we get 6(1 + 3y) - 3y = - 24 6 + 18y - 3y = - 24 15y = - 30 y = - 2 Substituting y = - 2 in ( i ),we get x = 1 + 3y x = 1 + 3(- 2) x = 1 - 6 x = - 5 x = - 5 and y = - 2 is the solution of given simultaneous equations. According to me both the methods are efficient and easy. It varies from individual to individual to decide which method is efficient. So my opinion to you is that learn both the methods and practice hard and try to master them. !!!HOPE I HELPED!!!!
belong in math
hmm nice haha
this is science....
Thanks kasim17

Not the answer you are looking for?

Search for more explanations.

Ask your own question